Assessing Lipid Profiles in the Saudi Population and Encouraging Early Lipid Screening: A Retrospective Single-center Experience - Khalid Mohammed Alharbi; Mashael Khalid Al-Ghanem; Sulaiman Mohammed Al-Zamel; Rayan Ahmed Alghamdi; Ghada Saleh Alnajdi; Marwa Abdullrahman Maghrabi; Yousef Alammari; Rayan Qutob (Journal of Nature and Science of Medicine)
Aim: This study was conducted to address the growing prevalence of cardiovascular diseases in Saudi Arabia by evaluating the lipid profiles and their relationship with sociodemographic factors such as age and sex. The aim was to identify the patterns of dyslipidemia in adults to inform early screening and targeted interventions. Settings and Design: This 1-year retrospective cohort study (January 1 to December 31, 2023) was conducted at Imam Mohammed Ibn Saud Islamic University’s healthcare facility in Riyadh, Saudi Arabia, involving adults aged 18 years and older. Subjects and Methods: The study included 5066 patients, excluding those under 18 and nonparticipants. Data collection captured sociodemographic details and lipid biomarkers, with Microsoft Excel used for data management. Statistical Analysis Used: The analysis utilized IBM’s SPSS version 26. Categorical data were expressed through frequency and percentage, with Chi-square, t-test, and analysis of variance used to compare the groups. P <0.05 denoted statistical significance. Results: The study enrolled 5066 patients, predominantly females (54%). Most patients were aged 31–45 years (35.6%). Mean high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, cholesterol, and triglycerides were 1.4 mmol/L, 3.3 mmol/L, 4.9 mmol/L, and 1.3 mmol/L, respectively. Significant links between lipid profiles and both gender and age were identified (P < 0.05). Conclusions: The study underscores the link between hyperlipidemia and coronary heart disease (CHD), highlighting the need for targeted interventions and screenings. By identifying hyperlipidemia’s associations with gender and age, the findings support early screening and intervention strategies to mitigate CHD risks.